Virtual Socialization about the Use of Family Medicinal Plants (TOGA) as an Alternative for Treatment - Ratna Mildawati; Bandhi Prasetya Nugroho; Fendy Prasetyawan; Ary Kristijono; Yuneka Saristiana; Isma Oktadiana; Arlan K Imran (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
The use of plants as a treatment solution, whether as preventive, promotive or curative therapy, is becoming popular again with the public due to the trend of back to nature medicine. Family Medicinal Plants (TOGA) are plants that have medicinal properties and grow around community yards which are managed by families and planted to meet the family's medicinal needs. The development and utilization of family medicinal plant cultivation is very necessary to support public health. This activity is carried out in an effort to provide knowledge to improve health. The target of this health education activity is housewives. The activity method carried out in this community service is outreach using the lecture method and using power point slides which contain explanations of several types of superior family medicinal plants and by inviting the public to plant TOGA. The success of this community service is assessed from the target number of participants of 75%, achievement of goals of 80%, achievement of material targets of 80% and success of planting TOGA at home 80%. The conclusion of this community service is that TOGA education increases people's knowledge and understanding of TOGA